Determination of Business Strategy with SWOT and AHP - Prita Prasetya (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to formulate strategic decision-making in the paint industry through the SWOT-AHP hybrid method. The calculated priorities of the SWOT factor can form a management approach to the company's main decisions. The calculated priorities of the SWOT factor can form a management approach to the company's main decisions. From the study results, it is expected to get an overview of the application of strategic analysis using the hybrid SWOT-AHP method based on influencing factors. AHP analysis using expert choice software. The SWOT analysis and AHP method results produce strategy priorities: (1) Build omni channel, (2) Build close relationships with all channels. (3) Build a close relationship with personal values, especially for Pareto stores. (4) Sales collaboration, (5) Start building infrastructure for digital business, (6) Formulate strategies to build collaborative relationships.